WORKSHOP ON BASIC ENGLISH CONVERSATION AND ISLAMIC INTEGRATION FOR ISLAMIC SCHOOL TEACHERS - Ahmad Syafi'i; Faisol Faisol (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2019)
The main objective of this community service activity is to facilitate a workshop on basic English conversation and Islamic integration for Islamic school teachers particularly for teachers in Madrasah Ibtidaiyah At Taqwa Sukodono. It was carried out due to limitation of so called worshops on those fore mentioned topics. The subject of this community service activity was teachers in Madrasah Ibtidaiyah At Taqwa Sukodono. The method implemented was guided workshop. It covers a workshop on motivation and insight of Islamic integration and a worshop on basic English conversation.